ON «STEP OF ALLOCATION» AND FORECASTING OF THE VEIN GOLD ORE BODIES - E. M. Nekrasov (Известия высших учебных заведений: Геология и разведка, 2018)
On the example of a number of domestic and foreign gold vein deposits it has been shown that the system of gold-ore bodies is located along some narrow local ore controlling displacements in a shape of veins. These veins are located at approximately equal distances from each other - at allocation step. This step varies from 30—70 m to 100— 250 m for different deposits. It allows forecasting of ore bodies at the flanks of the displacements and exploration by drilling. On the example of near-surface deposits it has been confirmed that such ore bodies can be formed at two vertical ore-bearing levels — upper and lower (deep). The upper level appears at very narrow vertical range of depths (100-300 m) near the paleosurface, presumably in the alumstone-adular-kaolinic metasomatites. Here the rhythmically-banded ores with low-grade gold are formed. At the lower (deep) level, the ore bodies can be formed in the interval of 600-1000 m and deeper from the paleosurface in the zones of tectonic breccia, crossing the metasomatites of the secondary quartzites type. They are more often to be the place of the localization of breccia structure ores with comparatively high-grade gold. So, at the near-surface deposits it is possible to explore the new (in particular, blind) ore bodies in allocation step distance from each other at two levels of mineralization, and, moreover, at the significant depth.